Modulation of pAKT and NF-κB pathways by Moringa oleifera silver nanoparticles: inducing apoptosis in cervical cancer cells - Naura Luviezka Choirunnisa; Debora Chris Kezia; Aiko Zavira Permana; Nik Ahmad Nizam Nik Malek; Fahrul Nurkolis; Happy Kurnia Permatasari (CyTA - Journal of Food)
Cervical cancer, predominantly caused by human papillomavirus (HPV) types 16 and 18, involves critical signaling pathways such as phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) and nuclear factor kappa B (NF-κB), promoting cell survival and inhibiting apoptosis. Conventional treatments often present severe side effects, prompting exploration of herbal alternatives. Moringa oleifera leaves, rich in phenolic compounds, have demonstrated anticancer potential. This study evaluated M. oleifera leaf extract combined with silver nanoparticles (AgNPs) against cervical cancer cells (HeLa cells) in vitro. Results indicated significant apoptosis induction through suppression of NF-κB and phosphorylated Akt (phospho-Akt) protein expression (p < .05). Ths, Moringa oleifera AgNPs represent a promising therapeutic option for cervical cancer, offering improved stability and reduced toxicity compared to traditional therapies.